Engaging With Farmers to Explore Correlates of Bovine Tuberculosis Risk in an Internationally Important Heritage Landscape: The Burren, in the West of Ireland - Clarke, AnneMarie; Byrne, Andrew W.; Maher, James; Ryan, Eoin; Farrell, Fidelma; McSweeney, Catherine; Barrett, Damien (Frontiers in Veterinary Science, 2022)
Bovine tuberculosis continues to be a pathogen of concern in several countries globally. National level research endeavours have informed risk management strategies and high-level policies. However, analysis of areas that have higher incidences of TB outbreaks has demonstrated how risk is not equally distributed, and local data collection, analysis and participatory engagement is required to develop tailored approaches. The Burren, an internationally important heritage landscape, has been an area of higher TB incidence for many years in Ireland, and owing to its unique geology and farming heritage a survey was developed to engage with local farmers to gain greater insight into farming practices and bTB control to inform tailored approaches. The survey gathered data on the farm and animal management approaches being used within the Burren, including local farming techniques like the use of “winterage” (grazing exposed limestone dominated uplands). Qualitative analysis of free text responses was undertaken. Quantitative data were then explored using statistical models to assess associations with recent (<3 years) self-reported bTB breakdown risk. There was a high response rate demonstrating a high degree of willingness to engage on the issue. Qualitative analysis suggested that wildlife and its management (culling and vaccination), testing quality, and its impact on the bTB scheme, and pessimism around eradication were important themes. Statistical analysis suggested that increasing bTB risk was primarily related to increasing herd-size and the percentage of herd owner’s land inaccessible to those attempting to locate badger setts. There was less evidence for associations relating to the amount of time, or which season (i.e. summer), farmers utilised “winterage”. The results of the study will feed back directly to local bTB management plans and further stakeholder engagement and is an exemplar for local tailoring of national control measures in situations of high incidences of TB outbreaks in particular areas.